Potential gains in life expectancy by eliminating deaths from cardiovascular diseases and diabetes mellitus in the working life ages among Slovak population - Beata Gavurova; Tatiana Vagasova (Health Economics Review, 2018)
Background: In recent years, high mortality from cardiovascular diseases (chronic ischemic heart disease, acute coronary syndrome, cerebrovascular diseases, atherosclerosis, hypertensive diseases) and diabetes mellitus have burdened economic and health system of the Slovak Republic considerably. By eliminating these deaths, the life expectancy could be prolonged. Since the mortality of population during working period has higher importance in terms of economic consequences of diseases, this article aims to assess the potential gains in life expectancy (PGLEs) of the Slovak population comparing the entire life span and working life-time. Methods: Data are obtained from the National Health Information Center mortality reports by sex during 1996-2014, and the method of constructing abridged life tables is used to compute the corresponding PGLEs. The added years, which would be gained by eliminating causes of deaths, are decomposed by the two sets of working age groups population (25-44 and 45-64 years). Results: The highest impact on life expectancy was recorded in chronic ischemic heart disease for both sexes aged 45-64 years (0.078 for males, 0.019 added years for females) over 1996-2014. However, they showed a small declining trend (- 16%) for males and even an increasing trend (2%) for females. At present, the labour force potential of working group (25-44 years) is most threatened by deaths from cerebrovascular diseases, while population of working age (45-64 years) by deaths from chronic ischemic heart disease. Relative importance of acute coronary syndrome for males (45-64 years) increased, when comparing the entire with working time life. Conclusions: The findings pose new and immediate challenges to policy makers and provoke discussion about prevention program strategies leading to increasing the life expectancy.
Keywords: 330; Life expectancy; Potential gains in life expectancy at birth; Working age groups; Mortality; Cardiovascular diseases; Diabetes mellitus